IMPLEMENTATION OF BAYES FOR DIAGNOSIS OF WOOD DISEASE IN CUTTING LIVESTOCK - Fawaydul Badris (Sean Institute, 2019)
Expert systems have been widely used to solve a problem in various fields such as medicine, mathematics, engineering, chemistry, pharmacy, computer science, business, law, education, and defense. If the expert system is associated with the doctor's ability to diagnose the patient's health, a computer system can be created that can identify and analyze the symptoms that arise in the patient and provide suggestions for treatment. Worming seems trivial, but if you look closely it turns out to have a serious impact on affecting the health of livestock which will ultimately have a direct impact on production decline. Cattle that have intestinal worms will experience nutritional deficiencies or nutrients, so that the resistance to disease will decrease, so it is easily attacked by other diseases, especially infectious diseases. Bayesian probability theory is one of the branches of mathematical-statistical theory that allows us to create a model of the uncertainty of events that occur by combining general knowledge with facts from observations.